Enzymatic synthesis and in vitro evaluation of folate-functionalized liposomes - Guo B; Xu D; Liu X; Yi J (Dove Medical Press, 2017)
Bohong Guo, Danqiao Xu, Xiaohong Liu, Jun Yi Department of Pharmaceutics, Guangdong Pharmaceutical University, Guangzhou, China Abstract: In this study, folate–poly(ethylene glycol)3400–cholesterol conjugates (FA–PEG–Chol) were enzymatically synthesized in one step and incorporated into liposomes to prepare folate (FA)-functionalized liposomes for targeted drug delivery. The FA-functionalized liposomes loaded with betulinic acid (BA) (FA-L-BA) were prepared by thin lipid film method. The FA-L-BA was characterized by their morphology, particle size, zeta potential, encapsulation efficiency (EE), stability, cell cytotoxicity and cellular uptake. The average size of FA-L-BA was 222±8 nm. The spherical particles exhibited a negative electrical charge of -20.12±1.45 mV and high EE of 91.61%±1.16%. The liposomes were taken up selectively by HepG2 cells. FA-L-BA showed enhanced cytotoxicity (50% inhibitory concentration [IC50] =63.07±2.22 µg/mL) compared to nontargeted control normal liposomes loaded with BA (L-BA; IC50 =93.14±2.19 µg/mL) in HepG2 cells in vitro. In addition, FA-functionalized liposomes loaded with Ir-1 (FA-L-Ir-1) showed significantly higher cellular uptake in HepG2 cells compared to nontargeted control normal liposomes loaded with Ir-1 (L-Ir-1). This novel approach for the liposomes surface modified with FA by a one-step enzymatic amidation was expected to provide potential application as a drug carrier for active targeted delivery to tumor cells. Keywords: enzymatic synthesis, liposomes, folate, surface modification, betulinic acid